Animal instinct [large type] - Rosenfelt, David (Rosenfelt, David. K Team novels., 2021)
"The K Team is back in the second installment in this spinoff series from bestselling author David Rosenfelt's beloved Andy Carpenter mysteries. Corey Douglas and his K-9 partner, a German shepherd named Simon Garfunkel, are recently retired police officers turned private investigators. Along with fellow former cop Laurie Collins and her investigating partner, Marcus, they call themselves the K Team, in honor of Simon. The K Team's latest case - a recent unsolved murder - gives Corey a chance to solve "the one that got away". Corey knew the murder victim from his time on the force, when he was unable to protect her in a domestic dispute. Now, he is convinced the same abusive boyfriend is responsible for her murder. With some help from Laurie's lawyer husband, Andy Carpenter, the K Team is determined to prove what the police could not, no matter the cost. What they uncover is much more sinister than they could have imagined."--Provided by publisher.